Fertilization, cover crop and harvest date: Their effects on soil physicochemical traits in an olive orchard in Southwestern Buenos Aires - Andrés, Busso, Mariano; Adrián, Rodríguez, Roberto; Graciela, Suñer, Liliana (International Journal of Sustainable Agricultural Research, 2025)
There is a scarcity of information on the effects of fertilization combined with cover crops on the soil physicochemical properties in olive orchards. We assess the effects of fertilization, cover crop, and harvest time on various soil characteristics in an olive (Olea europaea) orchard. Studies were conducted during the growing seasons of 2021/2022 and 2022/2023 in southwestern Buenos Aires, Argentina. The general experimental design in 2021/2022 and 2022/2023 was split plots. Fertilization treatments included an organic manure applied to the soil, inorganic fertilization applied to the soil or leaves of olive trees, and an unfertilized control. Additionally, a mixture of Vicia benghalensis with Avena sativa was either planted or not (control) as a cover crop. The study demonstrated that soil pH increased on average from mid-spring to mid-autumn during both studied growing periods. Soil organic matter, available phosphorus (P), and extractable potassium (K) were greater at 0-20 cm than at 20-40 cm soil depth. In 2022/2023, the percentage of soil organic matter appeared to be higher in areas with a cover crop than in those without, from early summer to early winter. Soil concentrations of ammonium, nitrate, P, and K were either similar or most often higher never lower in soils with organic and inorganic fertilizations compared to the inorganic foliar fertilization. These three types of fertilization showed greater nutrient concentrations than the unfertilized control. Finally, soil available P concentrations appeared to be higher in areas without vegetation cover than in those with a cover crop at 0-20 cm soil depth.